Approximation by a Complex Post-Widder Type Operator (Analysis in Theory and Applications, 2018)
In the present article, we deal with the so-called overconvergence phenomenonin $\mathbb{C}$ of a slightly modified Post-Widder operator of real variable, that is withthe extension of its approximation properties from the real axis in the complex plane.In this sense, error estimates in approximation and a quantitative Voronovskaya-typeasymptotic formula are established.